Encapsulation nanotechnologies - Mittal, Vikas (ill. : John Wiley & Sons, Inc., 2013)
"The process of encapsulation by which living creatures are engulfed in a protective shell is both well understood and widely used in industry. This work highlights the growing interest and use of nanotechnologies for the generation of nano-capsules or nano-containers with desirable properties and behaviors. It introduces readers to many significant processes and technologies that have been developed and applied successfully to generate encapsulated materials, addressing the high potential of these technologies and products in a large number of commercial processes"--